Financial and Labor Benefits of the Individual TB Risk Assessment Model for Annual TB Screening. (October 2020) - Sims, Kristin; Stienecker, Roger
Abstract : Background: Since 1991, US tuberculosis (TB) rates have declined, including among health care personnel (HCP). Non–US born persons accounted for approximately two-thirds of cases. Serial TB testing has limitations in populations at low risk; it is expensive and labor intensive. Method: We moved a large hospital system from facility-level risk stratification to an individual risk model to guide TB screening based on Tuberculosis Screening, Testing, and Treatment of US Health Care Personnel: Recommendations from the National Tuberculosis Controllers Association and CDC, 2019. This process included individual TB risk assessment, symptom evaluation, TB testing for M. tuberculosis infection (by either IGRA or TST) for HCP without documented evidence of prior LTBI or TB disease, with an additional workup for TB disease for HCP with positive test results or symptoms compatible with TB disease. In addition, employees with specific job codes deemed high risk were required to undergo TB screening. Result: In 2018, this hospital system of ~10, 000 employees screened 7, 556 HCP for TB at a cost of $348, 625. In 2019, the cost of the T Spot test increased from $45 to $100 and the cost of screening 5, 754 HCP through October 31, 2019, was $543, 057. In 2020, it is anticipated that 755 HCP will be screened, saving the hospital an estimated minimum of $467, 557. The labor burden associated with employee health personnel will fall from ~629.66 hours to 62.91 hours. The labor burden associated with pulling HCPs from the bedside to be screened will be reduced from 629.66 hours to 62.91 hours as well. Conclusion: Adoption of the individual risk assessment model for TB screening based on Tuberculosis Screening, Testing, and Treatment of US Health Care Personnel: Recommendations from the National Tuberculosis Controllers Association and CDC, 2019 will greatly reduce financial and labor burdens in healthcare settings when implemented. Funding: None Disclosures: None